A novel diazoresin/poly(N‐vinyl aminobutyric acid) covalent capillary coating for the analysis of proteins by capillary electrophoresis. Issue 6 (19th February 2014) - Yu, Bing; Jiao, Mingming; Cong, Hailin; Shu, Xi; Yang, Shujing
<x xml:space="preserve">Abstract</x> A novel method for the preparation of covalently linked capillary coatings of poly(N‐vinyl aminobutyric acid) (PVAA) obtained from hydrolyzed polyvinylpyrrolidone was demonstrated using photosensitive diazoresin (DR) as a coupling agent. A layer‐by‐layer self‐assembled film of DR and PVAA based on ionic bonding was first fabricated on the inner wall of capillary, then ionic bonding was converted into covalent bonding after treatment with UV light through a unique photochemical reaction of DR. The covalently bonded coatings suppressed protein adsorption on the inner surface of the capillary, and thus a baseline separation of lysozyme, cytochrome c, BSA, amyloglucosidase, and myoglobin was achieved using CE. Compared with bare capillary or noncovalently bonded DR/PVAA coatings, the covalently linked DR/PVAA capillary coatings not only improved the CE separation performance for proteins, but also exhibited good stability and repeatability. Due to the replacement of the highly toxic and moisture‐sensitive silane coupling agent by DR in the covalent coating preparation, this method may provide a green and easy way to make covalently coated capillaries for CE.